Biogenic and thermogenic terpenoid hydrocarbons as potential geochemical tools for the study of sedimentary organic matter in subtropical mangrove swamps. (November 2020) - Garcia, Marina Reback; Philp, Richard Paul; Martins, César C.
Abstract: Terpenoid hydrocarbons are ubiquitous in the marine environment and may be linked to natural synthetic activities after the original carbon skeleton of the biological precursor is retained. The terpenoid profile in pristine environments should have a biogenic signature. However, the widespread use of petroleum-derived products contributes to the inventory of hydrocarbons found in recent sediments, including the introduction of cyclic hydrocarbons with a thermogenic signature. Terpenoid hydrocarbons were examined from the mangrove sediments of the Paranaguá Estuarine System (PES), which is a subtropical system in the South Atlantic. Intensive tourism has affected the PES, and it is at high risk of contamination due to extensive urban development and harbour activity. The biogenic compounds (BIO) in the PES were predominantly composed of unsaturated derivatives from higher plants (oleanoids, lupanoids, ursanoids and taraxeroids) with a des-A configuration and bacterial hopanoids. Thermogenic compounds (TRM) were distributed throughout the PES, and the sum of thermogenic and biogenic compounds exhibited a similar distribution, with significant correlations between these compounds. To better assess anthropogenic sources of hydrocarbons in mangrove, a ratio of TRM/BIO was proposed. Ratios higher than 1.0 were found near Paranaguá port and in the Paranaguá bay area. An important touristic destination, Mel Island, also exhibited ratios higher than 1.0 in two locations. The proposed terpenoids ratio accurately assessed the low-level chronic inputs of anthropogenic hydrocarbons in the study area. This innovative approach may be applied to areas with high biogenic inputs of organic matter, where chronic low-level hydrocarbon contributions are not evident using n -alkanes and polycyclic aromatic hydrocarbons. Highlights: Terpenoid hydrocarbons from subtropical mangrove swamps were identified using mass spectrometry. Terpenoid hydrocarbons presented a mixed signature of biogenic and thermogenic sources. Terpenoids ratio provided an indication of chronic low-level hydrocarbon from human activities.